Pengaruh Flow Experience, Perceived Enjoyment, dan Price Perception terhadap Impulsive Buying dalam Fitur Live Shopping TikTok pada Generasi Z DKI Jakarta - Andini Destyaningrum; Annisa Lutfia; Bagus Kharismawan (Indo Publishing, 2026)
The shift in consumer behavior toward the digital ecosystem has driven the popularity of TikTok's Live Shopping feature, which integrates entertainment and interactive commerce. Intensive interaction and promotion within live broadcasts often trigger impulsive purchases, particularly among Generation Z in DKI Jakarta, known as the most active social media users. This study aims to analyze the influence of flow experience, perceived enjoyment, and price perception on impulsive buying in TikTok Live Shopping among Generation Z in DKI Jakarta. This study employs a quantitative approach with survey research method. The sample consists of Generation Z residing in DKI Jakarta who have watched or shopped through TikTok Live Shopping, obtained through purposive sampling. Data were collected using questionnaires and analyzed using multiple linear regression. The results show that flow experience and price perception have a positive and significant effect on impulsive buying, while perceived enjoyment has no significant effect. These findings indicate that impulsive purchasing decisions are more driven by deep psychological engagement and price perception rather than merely feeling entertained. This research is expected to serve as a reference for digital business practitioners in designing more effective marketing strategies